Characterizing a Novel Viral Sensitizer BI-D1870 - Watson, Margaret (Université d'Ottawa / University of Ottawa, 2019)
Oncolytic viruses (OVs) are an emerging cancer therapy that use an oncotropic virus to selectively infect and kill cancer cells, as well as stimulate long-lasting anti-tumor immune responses. In order to achieve high therapeutic efficacy, OVs need sufficient replication within the tumor tissue to mediate these effects. However, OV’s infectivity varies between different tumors and the host’s immune system can rapidly clear the virus, hampering treatment efficiency. Oncolytic virus sensitizers are chemical compounds that specifically enhance OV’s infectivity and efficacy. In our lab, I found that treatment of various cancer cell lines with BI-D1870, a pan-RSK (ribosomal S6 kinase) inhibitor, resulted in augmented Herpes Simplex Virus-1 (HSV1) and Vesicular Stomatitis Virus (VSVΔ51) infectivity. I also demonstrated that the effects of BI-D1870 on viral infection are virus-specific, and that RSK inhibition is not the primary target causing the enhancement of HSV1 and VSVΔ51 infection. Finally, BI-D1870 structural analogs were generated in an attempt to enhance the efficacy and selectivity of BI-D1870-based OV sensitizers. One of the analogs synthesized, KA-019, showed an improvement in the augmentation of OV infection over BI-D1870. As a genetically engineered strain of HSV1 has been approved by FDA for treatment of melanoma, the results of my project propose a novel viral sensitizer to improve viral replication within tumour cells with the hope of improving therapeutic efficacy.
Keywords: Oncolytic virus; Cancer therapy